The Third-Person Effect and Islamic Religiosity: Perceptions of Moral and Non-Moral Issues on Social Networking Sites among IIUM Students - Bawazir, Ala; Same'e, Somia Abdul; Mansoor, Hasan M. (Millah: Journal of Religious Studies, 2024)
Third-Person Effect theory (TPE) postulates that audiences deny the media's direct impact on themselves but perceive the same media as having a larger impact on others. This study examines TPE and its relationship with Islamic religiosity in shaping perceptions of moral and non-moral issues on social networking sites (SNS) among students at the International Islamic University Malaysia (IIUM). Another objective of this study is to determine how students perceive the effect of moral and non-moral issues in SNS on themselves compared to others. This study employed a quantitative design, with 357 students from the IIUM serving as respondents. The findings indicate that participants perceive moral issues as affecting others more than themselves, which is consistent with TPE. However, non-moral issues are perceived as influencing both the self and others. The results also indicate that Islamic religiosity positively affects the perceived impact of moral issues on others and non-moral issues on oneself in SNS. The data were analyzed using SPSS, with paired t-tests comparing self versus others' perceptions of moral and non-moral issues on SNS. The findings confirm that students perceive moral issues as having a greater impact on others than on themselves, aligning with TPE. Conversely, non-moral issues are perceived as influencing both the self and others, demonstrating SPE. The study also reveals that Islamic religiosity positively influences the perceived effect of moral issues on others and non-moral issues on oneself in SNS.